The Question of Housing in the scope of NEB goes South (EAAE Annual Conference Proceedings, 2023)
In the 20th century, technology gained world scale and accelerated our time. We believed that we were freeing ourselves from geographical, corporeal, and temporal ties. However, beyond all the climatic changes that we were devaluing, the covid-19 pandemic made our human and vulnerable side more evident. It became clear that we should move towards the 21st century, recognizing the paradigm shift that leads to a new urban condition as NEB strives to inspire.